2022
DOI: 10.31579/2641-0419/239
|View full text |Cite
|
Sign up to set email alerts
|

The Silverway Guidewire: An Observational Study on Successful Crossing when a Conventional J-tip Wire has failed

Abstract: Aim: The aim of this observational study was to evaluate the Silverway guidewire [Asahi Intecc Co.] that is designed to guide catheters during cardiac catheterization towards the aortic valve when the standard J-tip guidewire fails because of anatomical anomalies. Materials and Methods: A total of 50 consecutive patients, in which the Silverway guidewire was used, were analyzed: procedural characteristics, such as anatomical challenges, crossing of the vessel and deliverability of the catheters were prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…These anomalies are prone to bleeding and vascular complications and increased procedure time [ 7 , 8 ]. Other hydrophilic wires, such as Radifocus (Terumo, Tokyo, Japan) and Silverway (Asahi Intecc Co., Tokyo, Japan), are used to overcome these anatomical challenges [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These anomalies are prone to bleeding and vascular complications and increased procedure time [ 7 , 8 ]. Other hydrophilic wires, such as Radifocus (Terumo, Tokyo, Japan) and Silverway (Asahi Intecc Co., Tokyo, Japan), are used to overcome these anatomical challenges [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these technologies incorporates good deliverability, torque transmission, and safety [ 5 ]. We recently showed that the Silverway guidewire is successful at delivering the guidewire to the aortic valve when the J-tip guidewire fails due to anatomical obstacles [ 9 ].…”
Section: Introductionmentioning
confidence: 99%